Characterization of Streptomyces albus 18-kilodalton heat shock-responsive protein. - Servant, P (1995)
In Streptomyces albus during the heat shock response, a small heat shock protein of 18 kDa is dramatically induced. This protein was purified, and internal sequences revealed that S. albus HSP18 showed a marked homology with proteins belonging to the family of small heat shock proteins. The corresponding gene was isolated and sequenced. DNA sequence analysis confirmed that the hsp18 gene product is an analog of the 18-kDa antigen of Mycobacterium leprae. No hsp18 mRNA could be detected at 30 degrees C, but transcription of this gene was strongly induced following heat shock. The transcription initiation site was determined by nuclease S1 protection. A typical streptomycete vegetative promoter sequence was identified upstream from the initiation site. Disruption mutagenesis of hsp18 showed that HSP18 is not essential for growth in the 30 to 42 degrees C temperature range. However, HSP18 is involved in thermotolerance at extreme temperatures.